Two new species of Arisemus (Diptera: Psychodidae) from the Northeast Atlantic Forest, Brazil - Vilarinho, Naiara; Araújo, Maíra Xavier; Bravo, Freddy; dos Santos, Claudiney Biral (EntomoBrasilis, 2021)
Arisemus atlanticus Vilarinho, Araújo, Bravo & dos Santos sp. nov. and Arisemus benignoi Vilarinho, Araújo & Bravo sp. nov. are described from the Central Corridor of the Atlantic Forest. Currently, thirty-three species of the genus has been described from the Neotropical Region and only one from Brazil.